Adding heat to the live-high train-low altitude model: a practical insight from professional football. (26th November 2013) - Buchheit, M; Racinais, S; Bilsborough, J; Hocking, J; Mendez-Villanueva, A; Bourdon, P C; Voss, S; Livingston, S; Christian, R; Périard, J; Cordy, J; Coutts, A J
Abstract : Objectives: To examine with a parallel group study design the performance and physiological responses to a 14-day off-season 'live high-train low in the heat' training camp in elite football players. Methods: Seventeen professional Australian Rules Football players participated in outdoor football-specific skills (32±1°C, 11.5 h) and indoor strength (23±1°C, 9.3 h) sessions and slept (12 nights) and cycled indoors (4.3 h) in either normal air (NORM, n=8) or normobaric hypoxia (14±1 h/day, FiO2 15.2–14.3%, corresponding to a simulated altitude of 2500–3000 m, hypoxic (HYP), n=9). They completed the Yo-Yo Intermittent Recovery level 2 (Yo-YoIR2) in temperate conditions (23±1°C, normal air) precamp (Pre) and postcamp (Post). Plasma volume (PV) and haemoglobin mass (Hbmass ) were measured at similar times and 4 weeks postcamp (4WPost). Sweat sodium concentration ((Na + )sweat ) was measured Pre and Post during a heat-response test (44°C). Results: Both groups showed very large improvements in Yo-YoIR2 at Post (+44%; 90% CL 38, 50), with no between-group differences in the changes (−1%; −9, 9). Postcamp, large changes in PV (+5.6%; −1.8, 5.6) and (Na + )sweat (−29%; −37, −19) were observed in both groups, while Hbmass only moderately increased in HYP (+2.6%; 0.5, 4.5). At 4WPost, there was a likely slightly greater increase in Hbmass (+4.6%; 0.0, 9.3) and PV (+6%; −5, 18, unclear) in HYP than in NORM. Conclusions: The combination of heat and hypoxic exposure during sleep/training might offer a promising 'conditioning cocktail' in team sports.